Why is There Zero Women Candidate for Governor Election in West Java, Indonesia? - Malihah, Elly; Nurbayani, Siti; Anggraeni, Leni (Komunitas, 2020)
Democracy requires active public political participation. Sustainability of general elections is vitally important in democracy. As a developing country, Indonesia is still struggling to implement its democracy. Interesting phenomena in Indonesian democracy, the number of women who run their candidacy in an election is still limited. For instance, in West Java Province Regional Election, there are no women candidates for governor or vice governor. The political sociology perspective sees these phenomena as the patriarchal culture that the community prefers male leader to women. This research aims at understanding causes of why there are no female candidates in the general election in West Java. This research makes use of quantitative approach with survey method aimed to explain political views of West Java society about female candidates in a gubernatorial election. The area of the research covers West Java province, involving 500 respondents. The data was collected by using the questionnaire distributed by Google Form to people living in this area. The data were then analyzed by inferential statistics. This study indicates that West Java residents still hold strong ideology on gender differences, believing that a good leader should be male. Even in the smallest scope of institution, men is suppossed be a leader. In addition, there is a dichotomy between the public and the personal space for male and female duty. Women are suggested to stay at the private space, while male has a duty at the public sphere. It is also evidenced in the research that women voters have little tendency to elect the female candidates. This occurs not just because of their patriarchal cultural background, but also due to their education. It is indicated that even female voters had higher education, their tendency to elect the women candidate was still low.